Perlindungan Hukum Terhadap Pemilik Hak Eigendom Verponding Yang Belum Dikonversi Berdasarkan UU Nomor 5 Tahun 1960 Fisik Tanahnya Dikuasai Pihak Lain - Firman Haris Ginting; Resi Pranacitra (Neolectura, 2026)
During the Dutch colonial era, Eigendom Verponding was a land ownership right granted to native Indonesian citizens. The enactment of the Basic Agrarian Law (UUPA) in 1960, ratified by President Soekarno on September 24, 1960, mandated the conversion of such rights into Ownership Rights (HM) for Indonesian citizens or Building Use Rights (HGB) for foreigners, with a 20-year deadline from September 24, 1960, to September 24, 1980, as stipulated in UUPA Article 1 paragraph 3. Despite this, many eigendom verponding certificates remain unconverted, particularly among the Betawi community in Jakarta. Empirical research reveals instances where unconverted land, now occupied by company-owned buildings without compensation, raises questions about legal protection for original owners. Complementing this, normative juridical research examines whether these rights holders can still claim ownership over land physically controlled by others. The study links these issues to the Principle of Justice, ensuring rights are granted to rightful recipients and providing legal protection for land rights holders. This analysis underscores the need for equitable resolution in Indonesia's agrarian framework.